2008
DOI: 10.1007/s12149-007-0095-y
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of gallium-67 within mature and immature teratoma in pediatric patients: investigation for the uptake mechanism

Abstract: A high-uptake ratio of (67)Ga in benign teratoma was indicated. A close correlation between gallium scan and CT helps to ascertain whether (67)Ga uptake results from malignant and/or immature elements, or mature tissue components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Obtaining the correct pathology report is of crucial importance in this case. Performing a central pathomorphological examination can be helpful as it was mentioned by some of the studies [2,15,19,20,22,24,26,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining the correct pathology report is of crucial importance in this case. Performing a central pathomorphological examination can be helpful as it was mentioned by some of the studies [2,15,19,20,22,24,26,33].…”
Section: Discussionmentioning
confidence: 99%
“…A high-uptake ratio of gallium-67 in benign teratoma was indicated in one manuscript. A study by Gu et al revealed that GFAP (glial fibrillary acidic protein) is highly expressed in the nerve tissue of mature teratomas and is low in that of immature ones [33,34].…”
Section: Additional Examinations To Test the Immature Or Mature Charamentioning
confidence: 99%
“…In a 2015 study of 26 patients, for example, MRI proved superior to [ 18 F]FDG PET for distinguishing between benign (mature) and malignant (immature) teratomas (45). A previous study with [ 67 Ga]Ga SPECT provided similar results (46). The dense and fibrous nature of Brenner tumors-an ovarian lesion that can be benign or malignant-facilitates ready visualization via MRI, making it the current diagnostic gold standard (47).…”
Section: Adnexal Masses and Ovarian Cystsmentioning
confidence: 95%